2015
DOI: 10.1093/ejcts/ezv409
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic continuous machine perfusion enables preservation of energy charge and functional recovery of heart grafts in anex vivomodel of donation following circulatory death

Abstract: MP preservation of DCD hearts results in improved preservation of the energy and improved functional recovery of heart grafts compared with CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…13,14 Thus we did not rapidly rewarm the heart, instead allowing the circuit to warm to goal temperature during the first hour. Perfusion began at a pressure of 20 mmHg and at 20°C, and was increased slowly over the hour to the goal of 40–60 mmHg, and 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Thus we did not rapidly rewarm the heart, instead allowing the circuit to warm to goal temperature during the first hour. Perfusion began at a pressure of 20 mmHg and at 20°C, and was increased slowly over the hour to the goal of 40–60 mmHg, and 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…HMP improved the preservation of DCD heart grafts compared to SCS proven by superior postreperfusion contractility. The underlying mechanisms could include enhanced preservation of the energetic states and superior cellular integrity (87). Recently, Korkmaz-Icöz et al (88) demonstrated that HMP of aged donor hearts with MSCs protected against myocardial IRI in a rat model.…”
Section: Machine Perfusion Of Extended Criteria Donor Heart Graftsmentioning
confidence: 99%
“…Continuous perfusion flushes the organ of toxic metabolites and accumulated acids within the dilutional and buffering capacity of the preservation solution. The graft does not become truly ischemic and thus limits oxidative stresses and free radical mediated cellular damage associated with reperfusion injury . Perfusion devices also tightly regulate perfusate temperature, eliminating the detrimental effects of uncontrolled profound hypothermia.…”
Section: Potential Benefits and Limitations Of Machine Perfusion Presmentioning
confidence: 99%
“…The graft does not become truly ischemic and thus limits oxidative stresses and free radical mediated cellular damage associated with reperfusion injury. 24,[28][29][30][31] Perfusion devices also tightly regulate perfusate temperature, eliminating the detrimental effects of uncontrolled profound hypothermia. Additionally, cardiac allografts can be "conditioned" prior to transplantation by addition of therapeutic drugs, cytokines, gene products, or other agents.…”
Section: And Limitations Of Machine Perfusion Preservation Of Donor Hmentioning
confidence: 99%